Pemberdayaan Pengrajin Kana Tojeng Melalui Pemasaran E-Commerce Produk Anyaman Serat Lontara Songko Guru Desa Bontokassi - Nur Hayati, Lilis; Indra, Dolly; Djamereng, Asdar; Rahmat Suat, Wahyu Kadri; Saputra Scania, Muhammad Rifky; Rahma, Dewi Ernita (Jurnal Pemberdayaan Masyarakat, 2025)
This community engagement program aims to empower the "Kana Tojeng" craftswomen group in Bontokassi Village, Galesong Selatan District, Takalar Regency, through training in e-commerce-based marketing of woven products made from lontara fiber. The primary issues faced by the partners include limited understanding of digital marketing, lack of an established online business identity, and underutilization of e-commerce platforms. The method applied was an educational-participatory approach, consisting of observation, awareness sessions, hands-on training, and evaluation. The results show a significant improvement in participants' knowledge and skills, with pre-test scores at 50.30% and post-test scores reaching 86.19%. The program also resulted in the activation of e-commerce accounts and enhanced digital marketing capabilities among local artisans. Supporting factors included high participant enthusiasm and contextual learning materials, while limitations in digital infrastructure emerged as the main challenge. This initiative demonstrates that integrating information technology into local business management is an effective strategy for enhancing the competitiveness of culturally rooted products.